2011
DOI: 10.1063/1.3599854
|View full text |Cite
|
Sign up to set email alerts
|

Linking large piezoelectric coefficients to highly flexible polarization of lead free BaTiO3-CaTiO3-BaZrO3 ceramics

Abstract: We report a large d 31 piezoelectric coefficient and corresponding electromechanical coupling factor, K p , of 0.5Ba(Zr 0.2 Ti 0.8 )O 3 -0.5(Ba 0.7 Ca 0.3 )TiO 3 (BCTZ50) and 0.68Ba(Zr 0.2 Ti 0.8 )O 3 -0.32 (Ba 0.7 Ca 0.3 )TiO 3 (BCTZ32) lead-free piezoceramics. The piezoelectric coefficient, d 31 , reaches a high value of 200 pC/N for BCTZ50 at room temperature which is comparable to the one of the soft PZT. This confirms the previously reported d 33 for the same material. A useful way to achieve such perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 23 publications
(22 reference statements)
7
35
1
Order By: Relevance
“…We note that no extra reflections consistent with octahedral tilting are observed in any pattern in the current study. We therefore conclude that despite the introduction of the small Ca 2+ cation, no long-range octahedral tilts are introduced to the structure.To confirm the succession of 3 phase transitions for compositions beyond BCTZ32, we reconsidered the published dielectric data for BCTZ32 and BCTZ50 (ref 16 ) and we undertook further investigations of BCTZ20 and BCTZ40. In our earlier work 16 In order to confirm the suggested phase sequences and to assign a space group to the individual phase, full Rietveld refinements were performed on powder patterns collected for significantly longer times.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We note that no extra reflections consistent with octahedral tilting are observed in any pattern in the current study. We therefore conclude that despite the introduction of the small Ca 2+ cation, no long-range octahedral tilts are introduced to the structure.To confirm the succession of 3 phase transitions for compositions beyond BCTZ32, we reconsidered the published dielectric data for BCTZ32 and BCTZ50 (ref 16 ) and we undertook further investigations of BCTZ20 and BCTZ40. In our earlier work 16 In order to confirm the suggested phase sequences and to assign a space group to the individual phase, full Rietveld refinements were performed on powder patterns collected for significantly longer times.…”
mentioning
confidence: 99%
“…To confirm the succession of 3 phase transitions for compositions beyond BCTZ32, we reconsidered the published dielectric data for BCTZ32 and BCTZ50 (ref 16 ) and we undertook further investigations of BCTZ20 and BCTZ40. In our earlier work 16 In order to confirm the suggested phase sequences and to assign a space group to the individual phase, full Rietveld refinements were performed on powder patterns collected for significantly longer times.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 At room temperature, this boundary is at x $0.5 between a rhombohedral (R) and a tetragonal (T) phase, although the exact phase diagram in BCZT100x is still controversial. 9,[12][13][14][15][16][17][18] For example, a recent study 18 suggested that an intermediate orthorhombic (O) phase and a phase convergence region where four phases (R, O, T, and cubic (C)) may occur in a narrow temperature and compositional range. Thereby, the existence of such polymorphic regions seems to be a key to achieving the outstanding piezoelectric performance.…”
mentioning
confidence: 99%
“…325 In general, the system susceptibility to external parameters was considered to be a result of its high elastic softness that enables an easy polarization rotation along different crystallographic orientations. 332 This was mentioned as crucial for the development of enhanced electromechanical properties. High temperature poling was proved to be quite beneficial for attaining maximized properties.…”
Section: Electromechanical Propertiesmentioning
confidence: 99%